Extended Supply-Use Tables - Sourish Dutta (ZBW - Leibniz Information Centre for Economics, 2021)
The statistical challenges of globalization are profound. We cannot rely solely on national statistics to understand how economies work and how to create industrial policies focusing on competitiveness. It is necessary to see the whole. National statistics build pictures based on relationships between producers and consumers and the rest of the world. But these relationships, especially those with the rest of the world, have become increasingly more complex. There is an increasing need to consider global production within a global accounting framework. This implies a departure from the traditional role of international organizations as compilers of internationally comparable national statistics to bring together the national tables to create a global table (UN, 2019).
Keywords: F00; F01; F02; 330; Global Value Chains; Global Production Network; International Trade; Supply-Use Tables